5-Methylindole Potentiates Aminoglycoside Against Gram-Positive Bacteria Including Staphylococcus aureus Persisters Under Hypoionic Conditions - Sun, Fengqi; Bian, Mengmeng; Li, Zhongyan; Lv, Boyan; Gao, Yuanyuan; Wang, Yan; Fu, Xinmiao (Frontiers in Cellular and Infection Microbiology, 2020)
Antibiotic resistance/tolerance has become a severe threat to human and animal health. To combat antibiotic-resistant/tolerant bacteria, it is of significance to improve the efficacy of traditional antibiotics. Here we show that indole potentiates tobramycin to kill stationary-phase Staphylococcus aureus cells after a short, combined treatment, with its derivative 5-methylindole being the most potent compound tested and with the absence of ions as a prerequisite. Consistently, this combined treatment also kills various types of S. aureus persister cells as induced by the protonophore CCCP, nutrient shift, or starvation, as well as methicillin-resistant S. aureus (MRSA) cells. Importantly, 5-methylindole potentiates tobramycin killing of S. aureus persisters in a mouse acute skin wound model. Furthermore, 5-methylindole facilitates killing of many strains of gram-positive pathogens such as Staphylococcus epidermidis, Enterococcus faecalis, and Streptococcus pyogenes by aminoglycoside antibiotics, whereas it suppresses the action of aminoglycoside against the gram-negative pathogens Escherichia coli and Shigella flexneri. In conclusion, our work may pave the way for the development of indole derivatives as adjuvants to potentiate aminoglycosides against gram-positive pathogens.